2015
DOI: 10.11564/29-1-717
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the home-to-facility continuum of newborn and child health care through mHealth: Evidence from an intervention in rural Malawi

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Few studies have examined the impact of mHealth on participants’ confidence, satisfaction with health care or relationships with health workers, but available literature has found text message interventions to support higher satisfaction with antenatal care, higher confidence and lower anxiety during pregnancy, 33 increased empowerment to make informed decisions about health care, and increased knowledge in interactions with health workers. 34 The mMom project found that providing actionable and motivational information promoted participants’ active participation in care-seeking, which influenced the frequency and quality of their health system interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the impact of mHealth on participants’ confidence, satisfaction with health care or relationships with health workers, but available literature has found text message interventions to support higher satisfaction with antenatal care, higher confidence and lower anxiety during pregnancy, 33 increased empowerment to make informed decisions about health care, and increased knowledge in interactions with health workers. 34 The mMom project found that providing actionable and motivational information promoted participants’ active participation in care-seeking, which influenced the frequency and quality of their health system interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The mhealth strategy is imperative given the increasing use of mobile telecommunication in many countries in sub-Saharan Africa. The mhealth in Malawi reduced the burden of care-seeking in health facilities for childhood illnesses particularly fever [32]. This indicates that mhealth strategy would reduce facility-level workload of PHC workers.…”
Section: Combined Interventionsmentioning
confidence: 96%
“…Studies from Eastern Africa were the highest (n = 12): Tanzania [17][18][19][20][21][22], Rwanda [23,24], Ethiopia [25,26], Kenya [27] and Uganda [28]. There were five studies from Southern Africa: South Africa [29][30][31], Malawi [32], and Zimbabwe [33]. Studies conducted in Western Africa were 9: Nigeria [24,[34][35][36][37][38], Burkina Faso [39], Senegal [40], and Ghana [41].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson (1973) has long associated demography with facilities even though it was a study on the health sector where it was established that demographic characteristics, organisation of health services, ecological factors and social psychological factors influence the utilization of health services. In fact subsequent research on demographic characteristics and facilities in the health sector were even confined to the new-borns (Fotso, Bellhouse, Vesel, and Jezman, 2015).…”
Section: Introductionmentioning
confidence: 99%